Protagonismo sociocultural do Zé Pereira do Club dos Lacaios em Ouro Preto/MG: paisagem festiva e patrimônio intangível - Gabriela de Lima Gomes (2018)
This study is related to Cultural Geography and its possibilities of approximation with the preservation of heritage. The research focused on the resistance and resilience strategies of the Club dos Lacaios, a traditional carnival group from Ouro Preto, which celebrated 150 years of existence in 2017. We adopted an ethnographic/ ethnogeographic method, privileging the interpretative lines that identify the landscape as a new way of seeing the world and, then, presenting a practice of heritage preservation from the belonging and appropriation of space by individuals. The identification of the most important elements for the Club, its marks of tradition and resistance were what we call the Zé Pereira festive landscape. Concepts and applications of the landscape category were rescued to analyze the present and constituent elements of a group that, when organized in Zé Pereira do Club dos Lacaios, are able to signal the sociocultural identity of Ouro Pretos residents.